The role of phygital technologies in increasing the learning motivation of new generation students - Mironov L. V., Timoshenko E. V., Ishkova E. V. (Digitalization in the education system: best practices and implementation practices, 2025)
In their article, authors discuss how modern digital technologies can be used to increase motivation for learning. They examine the role of these technologies in modernizing educational systems, focusing on the synthesis of physical and digital reality. Based on an analysis of case studies of Russian educational platforms and universities, the article demonstrates how the integration of augmented reality (AR) and virtual reality (VR), gamification, and hybrid learning formats can help increase student motivation and develop digital skills. It also discusses the potential of digital technology to address challenges such as staff shortages and adapting pedagogical approaches for Generation Z students.
Keywords: мотивация; качество обучения; motivation; компетентностный подход; competence approach; дополненная реальность; виртуальная реальность; virtual reality; геймификация; гибридное обучение; gamification; цифровая трансформация образования; digital transformation of education; quality of learning; phygital technologies; learning formats; hybrid learning; augmented reality; фиджитал-технологии; форматы обучения